2004
DOI: 10.1128/cdli.11.1.63-69.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prostate Cancer Cell Colony Formation by the Flavonoid Quercetin Correlates with Modulation of Specific Regulatory Genes

Abstract: The natural product quercetin is a flavonoid found in many fruits and vegetables. Previous research has shown that quercetin has antitumor, anti-inflammatory, antiallergic, and antiviral activities. In the present investigation we studied the effect of quercetin on the ability of prostate cancer cell lines with various degrees of aggressive potential to form colonies in vitro. Specifically, we examined the molecular mechanisms underlying this effect, including the expression of cell cycle and tumor suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 32 publications
5
109
0
5
Order By: Relevance
“…Furthermore, quercetin was shown to inhibit cancer growth and induce apoptosis in animal models [Mouria et al, 2002]. Moreover, quercetin treatment has been associated with selective antiproliferative effects [Nair et al, 2004] and induction of cell death, predominantly through an apoptotic mechanism, in cancer cell lines but not in normal cells [Chowdhury et al, 2005]. Although the underlying mechanisms governing these effects are not yet fully understood, the available evidence collectively indicates that quercetin may be of therapeutic benefit in clinical settings, suggesting its potential use as an anticancer agent or an adjunct to current cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quercetin was shown to inhibit cancer growth and induce apoptosis in animal models [Mouria et al, 2002]. Moreover, quercetin treatment has been associated with selective antiproliferative effects [Nair et al, 2004] and induction of cell death, predominantly through an apoptotic mechanism, in cancer cell lines but not in normal cells [Chowdhury et al, 2005]. Although the underlying mechanisms governing these effects are not yet fully understood, the available evidence collectively indicates that quercetin may be of therapeutic benefit in clinical settings, suggesting its potential use as an anticancer agent or an adjunct to current cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have clearly shown that quercetin acts as a potent pleiotropic modulator in several physiological functions, showing different activities such as anti-proliferative effect in numerous cell lines [6,7], pro-apoptotic effect in lung carcinoma cell lines [8], and inhibitory effect of osteoclastic differentiation [9]. It is important to note that when the glycosylated forms of quercetin are assayed, there is usually a loss of activity in these effects in comparison with those obtained with the aglycone, due to the presence of the sugar moiety in the flavonoid structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Matsufuji et al [64] also showed that α-tocopherole was ranged from 0.49-5.40 mg/100 g FW. Finally, Isabelle et al [71] found that α-tocopherole content in Capsicum annuum var. grossum, green and red, was 3.06 and 24.76 µg vitamin E/g FW, respectively, and its content in Capsicum annuum var.…”
Section: Antioxidant Activities Vitamin C β-Carotene Vitamin E Andmentioning
confidence: 99%